I. Evaluation of apramycin soluble powder administered orally in piglets for the treatment of neonatal coliform diarrjoea: A pilot study - ΚΥΡΙΑΚΗΣ Σ. Κ.; ΣΙΜΟΣ Ε.; ΑΝΔΡΕΩΤΗΣ Ι. Σ.; ΤΣΑΛΤΑΣ Κ. (Journal of the Hellenic Veterinary Medical Society, 2019)
In a pilot study conducted in Greece, 30 litters of piglets suffering from a natural infection of neonatal coliform diarrhoea were randomly assigned to treatments containing 0,15 and 40 mg apramycin per I ml dose. Every piglet in each litter received orally a single dose of the same treatment once daily for 5 consecutive days. There was a dose related improvement for all parameters compared with the untreated control. Throughout the trial (14 days) mortality was 11.5% in the untreated group, 9.3% in the I5mg group and 5.4% in the 40 mg apramycin group. Apramycin at both levels significantly reduced sickness and diarrhoea. The average daily gain of the treated animals over the two week trial period was improved by 32% (P<0.05) and 4% for the 40mg and 15mg groups, respectively, as compared to controls. The liveweight gain per pig started was also improved by 41% (P<0.05) for the 40mg group and by 7% for the 15mg group in comparison with the untreated controls. A dose related improvement was also observed in both mean day 14 piglet health scores and mean piglet viability scores. The improvements were significant (P<0.05) for the 40mg apramycin treatment group. Escherichia coli was regularly cultured from rectal swabs taken both on day Ο and day 7 of the trial in all treatment groups. Strains of E.coli from intestinal contents from 2 of 3 sacrificed on day Ο piglets and 13 out of 18 piglets dying during the trial were positive for endotoxin (ST) production in the suckling mouse test. The study confirms that apramycin orally at 15mg and 40mg per piglet once daily for 5 days is effective in the treatment of neonatal coliform diarrhoea.